Phase transformations and phase stability in the Ti–44 at.%Al–(0–7 at.%)Mo system. (April 2022) - Musi, Michael; Clemens, Helmut; Stark, Andreas; Staron, Peter; Spoerk-Erdely, Petra
Abstract: Molybdenum is an excellent candidate to study the effect of β-stabilizing elements on the phase transitions in intermetallic γ-TiAl based alloys. In the present work, two model alloys based on the Ti–44Al (at.%) system containing 1 at.% and 5 at.% Mo are investigated. Examinations of the microstructures after casting and subsequent heat treatments reveal significant differences in the morphology and amount of the phases present and, thus, highlight the effect of Mo on the different phase transformations near and far from thermodynamic equilibrium. In-situ high-energy X-ray diffraction and differential scanning calorimetry were employed to identify the occurring phases and determine the phase transition temperatures in the two model alloys. Especially, the β phase was found to be strongly impacted by the Mo content of the alloys. While the β phase is only present at high temperatures in the Ti–44Al–1Mo alloy, it is thermodynamically stable from the liquidus temperature downwards to room temperature in the Ti–44Al–5Mo alloy. Long-term heat treatments for 30 days at 1000 °C were conducted to determine the phase equilibria at intermediate temperatures. Ultimately, the findings of this work were combined with data from literature to reassess the quasi-binary Ti–44Al–(0–7)Mo (at.%) phase diagram. Graphical abstract: Image 1 Highlights: Alloys with the compositions Ti–44 at.%Al–(1, 3, 5, 7 at.%)Mo are investigated. Solidification pathways of the alloys substantially change due to additions of Mo. Significant influence of Mo on the water-quenched microstructures is observed. A revised version of the Ti–44 at.%Al–(0–7 at.%)Mo phase diagram is presented.